Missed Plasmodium ovale Infections Among Symptomatic Persons in Angola, Mozambique, and Ethiopia. (18th May 2022) - Leonard, Colleen M; Hwang, Jimee; Assefa, Ashenafi; Zulliger, Rose; Candrinho, Baltazar; Dimbu, Pedro Rafael; Saifodine, Abuchahama; Plucinski, Mateusz; Rogier, Eric
Abstract: The majority of symptomatic malaria in sub-Saharan Africa is caused by Plasmodium falciparum . Infection with Plasmodium ovale is often not recorded and not considered clinically relevant. Here, we describe 8 cases of P ovale infection from 3 African countries—all of which were misdiagnosed at the presenting health facility.